Analysis of Online Single Submission Use Acceptance in Micro, Small and Medium Enterprise : (Study on MSME in Biromaru District, Sigi Regency) - Mawada Rahma Sari; Abdul Kahar; Femilia Zahra; Masruddin Masruddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the acceptance of the use of Online Single Submission (OSS) system technology in MSMEs in Biromaru District, Sigi Regency. Using a qualitative descriptive approach and a Technology Acceptance Model (TAM) framework, this study explores two main aspects: the perception of ease and usability of OSS systems. The data was collected through in-depth interviews with MSME actors. The results of the study show that the majority of MSME actors in Biromaru District have not used the OSS system independently due to low digital literacy, limited understanding of the OSS process, and dependence on third-party assistance. Thus, the successful implementation of the OSS system requires increased technical assistance, continuous socialization, and system improvements to be more user-friendly and adaptive to the conditions of MSME actors in the region.